Surgery in combination with systemic chemotherapy is associated with improved survival in stage IV gallbladder cancer. Issue 12 (December 2022) - Casabianca, Anthony S.; Tsagkalidis, Vasileios; Burchard, Paul R.; Chacon, Alexander; Melucci, Alexa; Reitz, Alexandra; Swift, David A.; McCook, Ashley A.; Switchenko, Jeffrey M.; Shah, Mihir M.; Carpizo, Darren R.
Abstract: Background: Gallbladder cancer (GBC) is the most common biliary malignancy frequently metastatic at diagnosis with poor prognosis. While surgery remains the standard for early-stage GBC, the role of surgery in patients with metastatic gastrointestinal cancers is expanding due to improvements in systemic therapies. We sought to evaluate the survival of patients with stage IV GBC undergoing surgery in an era of improved multi-agent systemic therapy. Methods: A retrospective review of the National Cancer Database was performed. Patients with stage IV GBC who underwent systemic therapy were included. Patients who received radiation therapy, palliative therapy or had missing survival data were excluded. Univariable and multivariable analysis was performed. Results: 4, 145 patients were identified between 2004 and 2016. Mean age was 69. Surgery combined with systemic therapy predicted improved median survival compared with chemotherapy alone (11.1mo versus 6.8mo, HR 0.65, p < 0.001). Additionally, receipt of treatment after 2011 predicted improved survival (HR 0.86, p < 0.001). Patients treated with multi-agent chemotherapy in combination with surgery were associated with the greatest hazard ratio benefit (0.40, p < 0.001) versus single agent therapy alone. Conclusion: Patients with stage IV gallbladder cancer treated with a combination of surgery and chemotherapy are associated with an improved overall survival compared to chemotherapy alone. Patients receiving care during the more recent era demonstrated improved survival. These results support a role for surgery in selected patients with stage IV gallbladder cancer receiving chemotherapy. Abstract : The role of surgery for stage IV gallbladder cancer is undefined. Review of the National Cancer Database predicts survival improvement for surgery combined with chemotherapy, favoring multi-agent regimens. In select patients with stage IV gallbladder cancer, surgery may be beneficial.